Dynamic Ornament: An Investigation of Responsive Thermochromic Surfaces in Architecture. (September 2013) - Meagher, Mark; van der Maas, David; Abegg, Christian; Huang, Jeffrey
This paper describes the use of environmental sensor data as a basis for the design of architectural ornament that takes on a distinctive appearance in response to the atmospheric conditions where it is located. Among the goals of the project were the identification of inexpensive fabrication methods that could be used to build responsive surfaces at the scale of a room, and the identification of material and tectonic strategies for integrating dynamic information displays in buildings. A series of prototypes were constructed to explore the benefits and limitations of thermochromic ink as a material for visualizing dynamic data, and a method is proposed for building thermochromic surfaces based on printed circuit boards (PCB's) that is cost-effective and allows the fabrication of large surfaces through tiling. The limitations of this method include high power consumption, a short lifespan and difficulties in controlling the surface temperature.